RIVER VALLEYS AS AN INDICATOR OF NEW TECTONIC MOVEMENTS - Abdurahmonov Adxamjon Sultonboevich; D. B. Olimjonov; S. F. Shamsiddinov; M. Zikriyoxujaeva (Journals Park Publishing, 2022)
In this аrticle it was cleared base on local materials learning the peculiavitiy of new tectonic acts in developing the landscapes.
Keywords: indication; landscape anomaly; oil and gas structure